Fluxnet Archive Product from Svartberget, 2014–2025 - Matthias Peichl; Mats Nilsson; Eric Larmanou; Paul Smith; Per Marklund; Giuseppe De Simon; Pernilla Lofvenius; Rowan Dignam; Jutta Holst; Meelis Molder; Tommy Andersson; Fabio Boschetti; et al. (Integrated Carbon Observation System, 2026)
Archive Product for Ecosystem Measurements. Fluxes, Meteo and ancillary measurements processed with the International standard FLUXNET procedure (ONEFlux suite) with different time aggregations.
Peichl, M., Nilsson, M., Larmanou, E., Smith, P., Marklund, P., De Simon, G., Lofvenius, P., Dignam, R., Holst, J., Molder, M., Andersson, T., Boschetti, F., Kozii, N., Linderson, M., Lindgren, K., Ottosson-Löfvenius, M. (2026). Fluxnet Archive Product from Svartberget, 2014–2025, FLUXNET, https://hdl.handle.net/11676/6APPPkAwbCF69Dx4gIGfRo8j
Keywords: Ecosystem Thematic Centre; carbon flux; meteo; none-ICOS; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap